Life cycle of a Posthodiplostomum species (Digenea: Diplostomidae) in Patagonia, Argentina - Ritossa, Luciano (2013)
In Patagonia, populations of the galaxiid fish Galaxias maculatus are parasitized by metacercariae of a species of Posthodiplostomum (Digenea: Diplostomidae). The aim of this work was to describe larval and adult stages of this species in experimental and natural hosts from an Andean Patagonian lake. Specimens of G. maculatus and the pulmonate snail, Anisancylus obliquus, were collected in Patagua Lake. The snails were isolated in individual containers to observe emergence of cercariae, dissected, and examined under a stereoscopic microscope to record sporocysts and cercariae. Fish were examined in order to obtain metacercariae; and uninfected fish from Gutiérrez Lake were exposed to cercariae from A. obliquus to obtain experimental metacercariae. Chicks and mice were infected with metacercariae from naturally infected G. maculatus to obtain experimental adults. Specimens recovered belong to Posthodiplostomum sp. on the basis of morphological features. This is the first description of sporocysts, cercariae, metacercariae and adults stages of a Posthodiplostomum species in Patagonia, including data about its natural intermediate hosts.